2013
DOI: 10.1039/c3cp52688g
|View full text |Cite
|
Sign up to set email alerts
|

Structural transitions of epitaxial ceria films on Si(111)

Abstract: The structural changes of a (111) oriented CeO2 film grown on a Si(111) substrate covered with a hex-Pr2O3(0001) interface layer due to post deposition annealing are investigated. X-ray photoelectron spectroscopy measurements revealing the near surface stoichiometry show that the film reduces continuously upon extended heat treatment. The film is not homogeneously reduced since several coexisting crystalline ceria phases are stabilized due to subsequent annealing at different temperatures as revealed by high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 54 publications
4
45
0
Order By: Relevance
“…In order to investigate the surface behaviors of the CeO 2 /Si thin films, the samples were annealed from 400 K to 1000 K in step of 50 K, and the annealing time was manually controlled according to the spectra. It is found that the surface compositions are only strongly temperature dependent, which is great different from Iordanova's results [19] and the reduction temperature is slightly higher than Wilkens' value [13]. It could be induced by different reactions occurring in the surface and interface in the thick film system.…”
Section: Surface Characterization Of Ceo 2 Thin Films During Vacuum Amentioning
confidence: 45%
See 3 more Smart Citations
“…In order to investigate the surface behaviors of the CeO 2 /Si thin films, the samples were annealed from 400 K to 1000 K in step of 50 K, and the annealing time was manually controlled according to the spectra. It is found that the surface compositions are only strongly temperature dependent, which is great different from Iordanova's results [19] and the reduction temperature is slightly higher than Wilkens' value [13]. It could be induced by different reactions occurring in the surface and interface in the thick film system.…”
Section: Surface Characterization Of Ceo 2 Thin Films During Vacuum Amentioning
confidence: 45%
“…Ce4d spectra as function of O2 exposure and annealing temperature. thin films deposited on Si substrates [7,13,21], which resulted from the diffusion of silicon to the surface. Compared with that of SiO 2 [22], the peak shifts toward lower binding energy, and corresponds to Si 3+ [14,23], which could originate from the products of solidstate reactions, such as SiO x or/and solid solution with Ce Si O bond, Ce Si oxide formation and so on.…”
Section: Surface Characterization Of Ceo 2 Thin Films During Vacuum Amentioning
confidence: 99%
See 2 more Smart Citations
“…Several intermediate bulk phases exist in the phase diagrams of ceria and praseodymia 22 which can be stabilized in pure ceria thin film systems. 23,24 Hence, we assume that this structure can be attributed to a reduced crystalline phase of the mixed oxide with low order. The samples with higher praseodymium content do not show this structure.…”
Section: Resultsmentioning
confidence: 99%